Research on Transverse Vibration Characteristics Analysis and Vibration Isolation Optimization of EMU Train Seats - Chuanhai Chen; Xu Jia; Xue Zhan; Tongtong Jin; Zonggui Ye; Zhijie Li; Junze Shi; Jinyan Guo; Hailong Tian; Liheng Zhang (Shock and Vibration)
This study aims to reduce the excessive transverse vibration of electric multiple unit (EMU) train seats in railway lines. Hence, the influence of seat vibration isolation components on the seat vibration is studied. The modal characteristics of the bogie, body, and seat of an EMU train are obtained via an on-the-spot running test and a whole vehicle bench test. In accordance with test results, design requirements of seat vibration isolation elements are proposed on the basis of single-degree-of-freedom vibration isolation theory. Then, the seat structure is optimized to improve the comfortable capacity. Contrastive test results show that the optimized vibration isolation measures can reduce the vibration of the seat and avoid resonance risk.